2023
DOI: 10.3390/molecules28155779
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Zymosan Treatment Induces IL15-Secreting Macrophages and KLRG1-Expressing NK Cells in Mice

Hyun Jung Park,
Sung Won Lee,
Yun Hoo Park
et al.

Abstract: Beta-glucan (β-glucan) is a natural polysaccharide produced by fungi, bacteria, and plants. Although it has been reported that β-glucan enhances innate immune memory responses, it is unclear whether different types of β-glucans display similar immune effects. To address this issue, we employed zymosan (β-1,3-glycosidic linkage) and pustulan (β-1,6-glycosidic linkage) to investigate their in vivo effects on innate memory immune responses. We examined the changes of innate memory-related markers in macrophages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…First, there are likely substantial differences in the relative availability of TLR2 binding sites between fragmented S. cerevisiae -derived cell walls (zymosan) and intact C. albicans yeasts 33 . Secondly, it is possible that complex regulatory mechanisms exist in vivo that dampen the TLR-mediated effects 34 ; this would also explain why others have observed that zymosan injection in vivo slightly increases intracellular TNF in splenic macrophages 35 . Thirdly, C. albicans interacts with multiple other host receptors in vivo, such as NLRP3, CR3, and mannose receptors, all of which have the potential to influence trained immunity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…First, there are likely substantial differences in the relative availability of TLR2 binding sites between fragmented S. cerevisiae -derived cell walls (zymosan) and intact C. albicans yeasts 33 . Secondly, it is possible that complex regulatory mechanisms exist in vivo that dampen the TLR-mediated effects 34 ; this would also explain why others have observed that zymosan injection in vivo slightly increases intracellular TNF in splenic macrophages 35 . Thirdly, C. albicans interacts with multiple other host receptors in vivo, such as NLRP3, CR3, and mannose receptors, all of which have the potential to influence trained immunity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…First, there are likely substantial differences in the relative availability of TLR2 binding sites between fragmented S. cerevisiae -derived cell walls (zymosan) and intact C. albicans yeasts (38). Secondly, it is possible that complex regulatory mechanisms exist in vivo that dampen the TLR-mediated effects (39); this would also explain why others have observed that zymosan injection in vivo slightly increases intracellular TNF in splenic macrophages (40). Thirdly, C. albicans interacts with multiple other host receptors in vivo , such as NLRP3, CR3, and mannose receptors, all of which have the potential to influence trained immunity (41).…”
Section: Discussionmentioning
confidence: 99%